O budismo pop de Coen rōshi: um estudo sobre a transplantação do zen ao Brasil, dos primeiros missionários à popularidade da monja - Magalhães, Breno Corrêa (2024)
The transplantation of Zen Buddhism from Japan to Brazil began with Japanese immigration. Sōtōshu established its first temple and mission in the country in the 1950s. In this thesis, we classify this process in three phases: [1] Ritual-liturgical service to the Japanese colonies and the search for academics (from 1955 to 1968); [2] Pioneering by Japanese masters - from 1968 to1995 and [3] cultural translation by Brazilian masters (from 1996). Without losing focus on her formal work at the institution that she belongs to - creating the Zendo Brasil community, opening practice spaces and ordaining disciples (monks, nuns and lay people) - the main objective of the research was to study the popularity that the Nun Coen rōshi has achieved through the use of the internet and social media as a tool for spreading the Dharma. Allied to this characteristic, her editorial work and the success of her public lectures constitute what we call pop Buddhism